2010
DOI: 10.1186/1471-2172-11-52
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-33 contributes to both M1 and M2 chemokine marker expression in human macrophages

Abstract: BackgroundInterleukin-33 is a member of the IL-1 cytokine family whose functions are mediated and modulated by the ST2 receptor. IL-33-ST2 expression and interactions have been explored in mouse macrophages but little is known about the effect of IL-33 on human macrophages. The expression of ST2 transcript and protein levels, and IL-33-mediated effects on M1 (i.e. classical activation) and M2 (i.e. alternative activation) chemokine marker expression in human bone marrow-derived macrophages were examined.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 31 publications
3
85
0
4
Order By: Relevance
“…39,40 This macrophage population represents the first line of defense against microbes breaching the intestine and ascendant gynecological infections. 22 As has been reported for other sites, 41-43 we observed that the peritoneal administration of IL-33 was able to promote an allergic like macrophage activation in the peritoneal tumor-associated macrophages. As reported previously for CD40 activated CD86 + activated macrophages in the microenvironment of pancreatic cancer, 44 or activated peritoneal macrophages were able to promote tumor cytotoxicity in vitro and delay tumor progression in vivo.…”
Section: Discusionsupporting
confidence: 80%
“…39,40 This macrophage population represents the first line of defense against microbes breaching the intestine and ascendant gynecological infections. 22 As has been reported for other sites, 41-43 we observed that the peritoneal administration of IL-33 was able to promote an allergic like macrophage activation in the peritoneal tumor-associated macrophages. As reported previously for CD40 activated CD86 + activated macrophages in the microenvironment of pancreatic cancer, 44 or activated peritoneal macrophages were able to promote tumor cytotoxicity in vitro and delay tumor progression in vivo.…”
Section: Discusionsupporting
confidence: 80%
“…The reduced levels of IRF4 protein observed are not reflected in the mRNA levels, suggesting that IRF4 may be posttranslationally regulated in RMs. IL-33 is a proinflammatory cytokine, alarmin, and amplifier of LPS activation (50)(51)(52)(53)(54). The lack of IL-33 expression in RMs may be important in limiting the amplification of LPS responses and M2 polarization through paracrine signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, выделяют популяцию атипичных Мф (табл. 1), которые демонстриру-ют характерный как для М1, так и М2 характер транскрипции генов [47]. Тканевые и опухоле-вые Мф также экспрессируют М2-маркеры [58].…”
Section: м1-и м2-макрофаги характеристика про-исхождение и роль в пunclassified